Hypochlorite accident in endodontic treatment: complication prevention and assistance - I. A. Gatilo; T. L. Kobylkina; M. G. Perikova; A. E. Bragin (LLC "Endo Press", 2021)
The outcome of endodontic treatment directly depends on the high-quality instrumental and medical treatment of root canals. The most effective, widespread and well-known antiseptic used for rinsing root canals is sodium hypochlorite. Unfortunately, in the process of irrigation complications arise in the form of sodium hypochlorite of various concentrations extrusion into the periapical region. We must not forget about the anatomical and topographic features of the structure of nearby structures, such as the mandibular canal and the maxillary sinus. The aim of the clinical case is to assess the depth of irrigant penetration into the periodontal area using radiography and to develop an algorithm for actions in the event of a hypochlorite accident.